A risk worth taking: Perceived risk as moderator of satisfaction, loyalty, and willingness-to-pay premium price. (September 2016) - Casidy, Riza; Wymer, Walter
Abstract: This research investigates the moderating role of perceived risk in the relationship between satisfaction, loyalty, and willingness to pay premium price (WTP). A total of 364 respondents were recruited from Amazon's Mechanical Turk panel. Financial, social, performance, and psychological risks have significant negative effects on the relationship between satisfaction and WTP, whereas only financial risks have significant negative effects on the relationship between loyalty and WTP. Using moderated mediation analysis, we found that the mediating effects of loyalty diminish significantly in high social risk conditions and diminish completely in high financial risk conditions. Highlights: We examine the moderating effects of risks on willingness to pay (WTP) antecedents. Social, performance, psychological risks moderates satisfaction – WTP relationship. Financial risks negatively moderates loyalty – WTP relationship. The mediating role of loyalty diminish significantly in high social risk conditions. The mediating role of loyalty diminish completely in high financial risk conditions.